ISOLATION AND STUDY ON ANTIBIOGRAM PATTERNS OF PSEUDOMONAS SPECIES ISOLATED FROM POST OPERATIVE INFECTION. - N.Naveenaa,; R.V, Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Postoperative wound infection is an important cause of infection in health care associated infection in hospitals. The most commonly seen bacterias in the postoperative infections are Staphylococcus aureus, Escherichia coli , Enterococci, Pseudomonas aeruginosa, and Streptococcus pyogenes. The risk of post operative infection is of prime importance because of emerging durg resistance in bacteria that delays the healing. Pseudomonas aeruginosa is a gram negative pathogen that causes health care associated infections.To isolate and study the antibiogram pattern of Pseudomonas sps isolated from post operatives infection.30 samples were collected from post-operative infection and cultured for the presence of Pseudomonas. The antibiotic sensitivity test was performed to find out the antibiogram susceptibility pattern of the Pseudomonas isolated,Out of 30 samples collected from post operative infections, Pseudomonas species was isolated from 6 samples. They all showed sensitivity towards ciprofloxacin, cefepime, amikacin, meropenem, aztreonam and resistance towards imipenem, colistin, ofloxacin and cefoperazone.KEYWORDS:  ,, ,